2014
DOI: 10.1007/s12088-014-0488-2
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Biosynthesis Gene Disruption in Methicillin-Resistant Staphylococcus aureus (MRSA) as Potential Mechanism for Reducing Antibiotic Resistance

Abstract: The aim of this study was to evaluate the effectiveness of the membrane biosynthesis gene disruption in MRSA (methicillin resistant Staphylococcus aureus) using sea cucumber extract (SBE). The disruption of membrane biosynthesis gene also known as multiple peptide resistance gene (mprF), would impair the lysylation of cell membrane phosphatiglycerol and thus reduce antibiotic resistance in MRSA. The membrane permeability assay was done to determine the degree of homology of the SBE treated RNA and the resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Therefore, our nding coincide with the previous report of Valliammai et al that the increase in membrane uidity in S. aureus enhances sensitivity to the membrane targeting antibiotic polymyxin B [34]. Also, many previously done work have reported that the membrane damage led to higher susceptibility of S. aureus towards antibiotics [35,36]. Therefore, during the current investigation, a greater zone of antibiotic inhibition may have been also in uenced by the increase in membrane uidity.…”
Section: Gmm and Mo Vocs Alters The S Aureus Membrane And Increase Ba...supporting
confidence: 91%
“…Therefore, our nding coincide with the previous report of Valliammai et al that the increase in membrane uidity in S. aureus enhances sensitivity to the membrane targeting antibiotic polymyxin B [34]. Also, many previously done work have reported that the membrane damage led to higher susceptibility of S. aureus towards antibiotics [35,36]. Therefore, during the current investigation, a greater zone of antibiotic inhibition may have been also in uenced by the increase in membrane uidity.…”
Section: Gmm and Mo Vocs Alters The S Aureus Membrane And Increase Ba...supporting
confidence: 91%
“…There are two types of MRSA infection, hospital associated (HA) and community associated (CA) both differing in their epidemiology, DNA sequence, populations infected and sites of infection [5]. MRSA confers resistance to almost all commercially available antibiotics except vancomycin and teicoplanin [6,7]. For many years, vancomycin has been used as the effective drug for MRSA infections.…”
Section: Introductionmentioning
confidence: 99%